Risk for sexually transmitted diseases among Police officers - Pinheiro, Flávia KB (2011)
Introduction: in sexuality studies, it is important to investigate the prevalence and risk factors for infection with sexually transmitted diseases (STDs) due to the high morbidity and mortality rates related to such diseases, especially with regard to HIV. Objective: to verify the presence of risk factors for the occurrence of sexually transmitted diseases (STDs) among male police officers. Methods: a cross-sectional study was conducted between July and September 2010. Male police officers who agreed to participate were included in the study. A self-administered and anonymous questionnaire was used to collect data on sociodemographic characteristics, sexual behavior and history or presence of STD. Data was inserted into the Epidata version 3.1 and statistical analysis was performed using SPSS version 18.0. results: 193 policemen participated in the study. Mean age was 36.3 (SD ± 7.7) years. Predominantly, They were predominantly caucasians (80.8%), catholic (62.7%), married (62.7%), and heterosexual (94.3%). Of the total, 34 policemen had previous STDs, and gonorrhea was the most commonly reported. With regard to behavioral factors, 67.4% of the policemen were or had no religion and only 24.4% used condom during sexual intercourse. The incidence of STDs was associated with the lack of condom use, homosexuality or bisexuality, sex with sex workers, extramarital affairs, multiple partners, drug use and alcoholism. Conclusion: the results suggest that this population is largely suscetible to contracting STDs, by having multiple risk factors.